2022
DOI: 10.3389/fnetp.2021.755685
|View full text |Cite
|
Sign up to set email alerts
|

Criticality in the Healthy Brain

Abstract: The excellence of the brain is its robustness under various types of noise and its flexibility under various environments. However, how the brain works is still a mystery. The critical brain hypothesis proposes a possible mechanism and states that criticality plays an important role in the healthy brain. Herein, using an electroencephalography dataset obtained from patients with psychotic disorders (PDs), ultra-high risk (UHR) individuals and healthy controls (HCs), and its dynamical network analysis, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Frontiers in Network Physiology frontiersin.org modeling of epileptic-seizure-related synchronization phenomena (Gerster et al, 2020), where a part of the brain synchronizes, it turned out that such a cross-coupling is important. The subtle interplay of excitatory and inhibitory interaction is typical of the critical state at the edge of different dynamical regimes in which the brain operates (Massobrio et al, 2015;Shi et al, 2022), and gives rise to partial synchronization patterns which are not found otherwise.…”
Section: Neural Network Modelmentioning
confidence: 99%
“…Frontiers in Network Physiology frontiersin.org modeling of epileptic-seizure-related synchronization phenomena (Gerster et al, 2020), where a part of the brain synchronizes, it turned out that such a cross-coupling is important. The subtle interplay of excitatory and inhibitory interaction is typical of the critical state at the edge of different dynamical regimes in which the brain operates (Massobrio et al, 2015;Shi et al, 2022), and gives rise to partial synchronization patterns which are not found otherwise.…”
Section: Neural Network Modelmentioning
confidence: 99%
“…Besides, an alternation between synchronization and desynchronization reflects the variability of the system; this can be seen as a critical state between a fully synchronized and a desynchronized state. It is known that the brain is operating in a critical state at the edge of different dynamical regimes (Massobrio et al, 2015;Shi et al, 2022), exhibiting hysteresis and avalanche phenomena as seen in critical phenomena and phase transitions (Kim et al, 2018;Ribeiro et al, 2010;Steyn-Ross and Steyn-Ross, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also in the modeling of epileptic-seizure-related synchronization phenomena (Gerster et al, 2020), where a part of the brain synchronizes, it turned out that such a cross-coupling is important. The subtle interplay of excitatory and inhibitory interaction is typical of the critical state at the edge of different dynamical regimes in which the brain operates (Massobrio et al, 2015;Shi et al, 2022), and gives rise to partial synchronization patterns which are not found otherwise.…”
Section: Neuronal Network Modelmentioning
confidence: 99%
“…The data are provided in electronic supplementary material [44]. The codes for calculating embedding entropy/conditional embedding entropy are available at .…”
Section: Data Accessibilitymentioning
confidence: 99%